WORLD EXPERIENCE AND NATIONAL FEATURES OF IMPROVING THE AUTHENTICATION OF SOCIAL VULNERABLE GROUPS - Vasikovich, Vakhabov Abdurahim (International Journal of Psychosocial Rehabilitation, 2020)
The article evaluates the practice of identifying socially vulnerable segments of the population, analyzes the methods used by international economic organizations to identify the disadvantaged population, and provides information on the priority areas of action in Uzbekistan.